Sonochemical synthesis of a copper reduced graphene oxide nanocomposite using honey and evaluation of its antibacterial and cytotoxic activities - Nur Afini, Ismail; Kamyar, Shameli; Siti Nur Amalina, Mohamad Sukri; Hara, Hiofumi; Teow, Sin Yeang *; Moeini, Hassan (Frontiers Media, 2022)
The combination of graphene-based materials and inorganic nanoparticles for the enhancement of the nanomaterial properties is extensively explored nowadays. In the present work, we used a sonochemical method to synthesize a copper/reduced graphene oxide (Cu/RGO) nanocomposite using Australian honey and vitamin C as capping and reducing agents, respectively. The honey-mediated copper/reduced graphene oxide (H/Cu/RGO) nanocomposite was then characterized through UV-visible, XRD, HRTEM, and FTIR analysis. The copper nanoparticles (Cu-NPs) in the nanocomposite formed uniform spherical shapes with a size of 2.20 ± 0.70 nm, which attached to the reduced graphene oxide (RGO) layers. The nanocomposite could suppress bacterial growth in both types of bacteria strains. However, in this study, the nanocomposite exhibited good bactericidal activity toward the Gram-positive bacteria than the Gram-negative bacteria. It also showed a cytotoxic effect on the cancer colorectal cell line HCT11, even in low concentrations. These results suggested that the H/Cu/RGO nanocomposite can be a suitable component for biomedical applications.